UPAYA INDONESIA DALAM MEMPROMOSIKAN ANGKLUNG SEBAGAI WARISAN BUDAYA INDONESIA MELALUI HOUSE OF ANGKLUNG DI AMERIKA SERIKAT (2010-2015) - Wahyuni, Yuli Tri; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is a study of contemporary which discussing about the efforts of Indonesia in promoting Angklung as one of Indonesan cultural heritage through House of Angklung in the United States. In November 2010, Angklung has been declared by UNESCO as a world cultural heritage. House of Angklung is an organization of Angklung lovers in the United States. This is originally an association of Sundanese citizens who lived in the United States. In April 2010, the association changed its name to House of Angklung which was not only teach Angklung but also learning about Indonesian culture and language. The result of this research shows that the effort of Indonesia in promoting Angklung as Indonesian cultural heritage through House of Angklung runs effective. Indonesia invites House of Angklung to cooperate in promoting Angklung, among others, by facilitating the training or practice ground which is located on Indonesian Embassy, lending Angklung, finding funds, giving transportation and information about humanist.Keywords: House of Angklung, Cultural Heritage, Cultural Diplomacy, UNESCO.